Profils des jeunes adultes en situation de « raccrochage » au Québec. Le cas particulier des jeunes femmes inscrites en Centre d'Éducation des Adultes - Aude Villatte; July Corbin; Julie Marcotte (Nantes Université, 2014)
Each year, a sizable portion of French Canadian students (17%) leave high school without a diploma or qualification (Statistical Institute of Quebec, 2013). However, the proportion of dropouts who make a comeback at school through Adult Education Settings (AES), about 25%, can qualify the extent of this phenomenon (Marcotte, Cloutier & Fortin, 2010). This manuscript proposes a description of these Quebec's school settings and the psychosocial profiles of students enrolled in them. The profile of young women in these school settings is of particular interest since they represent a highly vulnerable group with unique characteristics. More specifically, their high school interpersonal experiences, their psychological adjustment in AES and the positive influence of AES in revaluating the way they see school and themselves are distinctive of these women. Results are discussed in light of the importance of developing and valorizing school settings that favor returning to school in Quebec and elsewhere to promote psychosocial adjustment of young adults.